Feed Your Mind How Does Nutrition Modulate Brain Function throughout Life? - Bosch-Bouju, Clémentine; Layé, Sophie; Pallet, Véronique (IntechOpen, 2019)
Nutrition is an environmental factor modulating physiology throughout life and especially brain function. Nutrients in the brain can either fuel brain cells, contribute to tissue architecture, or initiate signaling pathways through their derivatives. Nutrients ultimately participate in brain development, cognitive and emotional behaviors, and can influence the susceptibility to develop brain pathologies. This book is a selection of current research on the impact of diet on brain function. Chapters include the role of lipids and glucose on the brain, nutrition and autophagy, and consequences of enteral feeding on brain-gut interactions. Taken together, this book targets all scientists, clinicians, teachers, and students eager to learn more about the impact of nutrition on brain function.